2008
DOI: 10.1021/bi702405a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serine 167 in Human Indoleamine 2,3-Dioxygenase: A Comparison with Tryptophan 2,3-Dioxygenase

Abstract: The initial step in the l-kynurenine pathway is oxidation of l-tryptophan to N-formylkynurenine and is catalyzed by one of two heme enzymes, tryptophan 2,3-dioxygenase (TDO) or indoleamine 2,3-dioxygenase (IDO). Here, we address the role of the conserved active site Ser167 residue in human IDO (S167A and S167H variants), which is replaced with a histidine in other mammalian and bacterial TDO enzymes. Our kinetic and spectroscopic data for S167A indicate that this residue is not essential for O 2 or substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
118
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(129 citation statements)
references
References 16 publications
9
118
2
Order By: Relevance
“…EPR spectroscopy has shown that ferric hTDO is a mixture of high-spin iron (g values of 5.71, 2.01) and low-spin iron (g values of 2.89, 2.30, 1.62), which correlated with observations for ferric hIDO high-spin iron (g values of 5.82, 1.99) and low-spin iron (g values of 2.85, 2.27, 1.62) [12,20]. The spectroscopic features of the low-spin species are consistent with those expected for a bis-histidine species [21,22], but this assignment is problematic for hIDO in which there is no active-site histidine residue (see above).…”
Section: Binding Of L-and D-tryptophansupporting
confidence: 77%
See 1 more Smart Citation
“…EPR spectroscopy has shown that ferric hTDO is a mixture of high-spin iron (g values of 5.71, 2.01) and low-spin iron (g values of 2.89, 2.30, 1.62), which correlated with observations for ferric hIDO high-spin iron (g values of 5.82, 1.99) and low-spin iron (g values of 2.85, 2.27, 1.62) [12,20]. The spectroscopic features of the low-spin species are consistent with those expected for a bis-histidine species [21,22], but this assignment is problematic for hIDO in which there is no active-site histidine residue (see above).…”
Section: Binding Of L-and D-tryptophansupporting
confidence: 77%
“…Hence, reduction potentials for the Fe 3+ /Fe 2+ couple of hTDO in the absence (−92 mV) and presence (−76 mV) of substrate are not very different, which is also consistent with the idea that there is no preferential binding of the substrate in one or the other oxidation state. In contrast, the substrate-binding affinity of ferric hIDO (K d ≈ 200-300 μM) is ∼20-fold lower than for the ferrous form (K m ≈ 10 μM), so that ferrous hIDO has a much higher affinity for L-tryptophan [14,20]. These binding affinities for hIDO are similarly correlated in the redox data since there is an ∼80 mV positive shift in the reduction potential on binding of substrate, demonstrating stabilization of the ferrous form of the enzyme upon binding of substrate.…”
Section: Binding Of L-and D-tryptophanmentioning
confidence: 91%
“…These data support the scenario that hIDO binds O 2 prior to L-Trp binding during the multiple turnovers under physiological conditions. It also provides a rational explanation for the finding that the enzyme turns over efficiently in the presence of Ͻ50 M L-Trp (29,56), despite the fact that under this condition only Ͻ5% ferrous enzyme is in the L-Trp-bound form (based on the K d (L-Trp) of 400 M) (31). The preferential binding of O 2 prior to substrate binding is unique as compared with the other heme dioxygenase, TDO, and monooxygenase type of enzymes (such as P450s), in which substrate-binding precedes O 2 binding (1,11).…”
mentioning
confidence: 91%
“…(13 M) (56). However, the K m (L-Trp) is 15 M (39), 25-fold lower than the K d (L-Trp) of the ligand-free ferrous enzyme (400 M) (31).…”
mentioning
confidence: 98%
“…these enzymes catalyze the same dioxygenase reaction and contain similar heme active sites (8 -10), IDO and TDO are distinct enzymes that are monomeric and homotetrameric, respectively, share only 10% sequence identity (9), and show differences in tissue distribution, protein structure, substrate specificity and binding, and enzyme reactivity (11)(12)(13).…”
mentioning
confidence: 99%